Warriors : Exile From Shadowclan - Book 3 Exile from ShadowClan - Jolley, Dan; Hunter, Erin; Barry, James L., 1979- (New York, NY : Harper Alley, an imprint of HarperCollinsPublishers, 2022)
On the verge of a bitter leaf-bare, ShadowClan stands on the brink of its own destruction. Its leader, Brokenstar, is bent on nothing but battle and revenge. His former mentor, retired warrior Nightpelt, hasn't had an easy path, but he has always put his Clanmates first. So when Brokenstar banishes Nightpelt and the rest of ShadowClan's elders to the farthest edges of Clan territory, Nightpelt is shocked at his cruelty. But he's determined to ensure he and his fellow exiles survive the coming frost--and live to reclaim the ShadowClan they've always known.
Keywords: Cats -- Comic books, strips, etc; Clans -- Comic books, strips, etc; Animals -- Comic books, strips, etc; Survival -- Comic books, strips, etc; Revenge -- Comic books, strips, etc; Cats -- Fiction; Clans -- Fiction; Animals -- Fiction; Survival -- Fiction; Revenge -- Fiction; Action and adventure comics; Fantasy comics; Animal fiction; Graphic novel adaptations; Graphic novels; Comics (Graphic works)